2021
DOI: 10.3390/ma14020428
|View full text |Cite
|
Sign up to set email alerts
|

Wear Behavior Characterization of Hydrogels Constructs for Cartilage Tissue Replacement

Abstract: This paper aims to characterize the wear behavior of hydrogel constructs designed for human articular cartilage replacement. To this purpose, poly (ethylene glycol) diacrylate (PEGDA) 10% w/v and gellan gum (GG) 1.5% w/v were used to reproduce the superior (SUP) cartilage layer and PEGDA 15% w/v and GG 1.5% w/v were used to reproduce the deep (DEEP) cartilage layer, with or without graphene oxide (GO). These materials (SUP and DEEP) were analyzed alone and in combination to mimic the zonal architecture of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Both materials are generally featured by a nanometric thickness and a large lateral dimension, from hundreds of nanometers up to tens of microns, making them versatile for several applications. For example, GO and rGO have been used as electrical dopant agents in conductive composite materials [ 5 , 6 ], for mechanical reinforcement of polymeric matrices [ 7 ], or as lubricant agents to improve the wear of scaffolds to be used as substitutes for load-bearing joints [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both materials are generally featured by a nanometric thickness and a large lateral dimension, from hundreds of nanometers up to tens of microns, making them versatile for several applications. For example, GO and rGO have been used as electrical dopant agents in conductive composite materials [ 5 , 6 ], for mechanical reinforcement of polymeric matrices [ 7 ], or as lubricant agents to improve the wear of scaffolds to be used as substitutes for load-bearing joints [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…GO with laminar structure presents peculiar self‐lubricating and antiwear features and contributes to guaranteeing the lubrication of surfaces. Affatato et al investigated compositions of PEGDA and GG hydrogels with or without embedded GO in order to evaluate its effect within the polymeric network with the aim of articular cartilage replacement 119 . They showed that the presence of 0.01% GO helps to maintain the hydrogel construct's properties.…”
Section: Graphene‐based Nanocomposites For Tissue Engineering Applica...mentioning
confidence: 99%
“…Hydrogels are water-swollen, 3D materials that can be injected in a minimally invasive manner in the joint [ 16 ]. In OA, hydrogels are interesting materials because of their good biocompatibility and biodegradability, mechanical and lubricant functions, hydrophilicity (for swelling and hydration), and minimally invasive approach.…”
Section: Introductionmentioning
confidence: 99%